The Upregulation of Toll-Like Receptor 3 via Autocrine IFN-β Signaling Drives the Senescence of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Through JAK1 - Lee, Hyang Ju; Choi, Bongkun; Kim, Yongsub; Lee, Sang Eun; Jin, Hye Jin; Lee, Hee-Seop; Chang, Eun-Ju; Kim, Seong Who (Frontiers in Immunology, 2019)
Although mesenchymal stromal cells (MSCs) are among the most promising cell sources for cell-based therapies and regenerative medicine, the decline in their function with age due to cellular senescence limits their therapeutic applications. Unveiling the underlying mechanism of MSC senescence is therefore of substantial interest with regard to advancing MSC-based cell therapies. We here show that the induction of human MSC senescence causes the predominant upregulation of Toll-like receptor 3 (TLR3). Subsequent TLR3 activation by polyinosinic-polycytidylic acid triggers the prominent features of senescence. Using a clustered regularly interspaced short palindromic repeats/Cas9 library screening system, we identified Janus kinase 1 (JAK1) as the candidate regulatory factor for TLR3-mediated MSC senescence. A JAK1 deficiency blocked the MSC senescence phenotype upon TLR3 activation and TLR3 induction. Targeting the JAK1 pathway using chemical JAK1 inhibitors also significantly suppressed TLR3-mediated MSC senescence. Importantly, we further observed that MSC senescence is driven by a senescence-associated secretory phenotype (SASP) and that interferon-beta (IFN-beta) is therefore a component of TLR3-dependent SASP, whereby its autocrine actions upregulate TLR3 and suppress cell proliferation. A JAK1 depletion significantly interrupted these effects of IFN- beta, indicating that JAK1 is a signaling mediator linking IFN- beta activity to TLR3 expression and the process of MSC senescence. Collectively, our findings provide new mechanistic insights into MSC senescence by revealing the role of an autocrine regulatory loop of SASP evoked by TLR3 activation.